Gender identity in 10 year-old children’s humour stories - Galindo Merino, Mª Mar (Círculo de Lingüística Aplicada a la Comunicación, 2017)
This paper analyzes 148 humorous narratives created by nine and ten-year-old boys and girls. The writings belong to the CHILDHUM corpus, explored here to look for gender differences in the use of linguistic strategies aimed to produce humor. These linguistic marks are interpreted as a sign of child metapragmatic competence. Thus, we first present the relation between humor production and metapragmatic competence, to analyze humor from a gender perspective afterwards. Then, we focus on children production and their metalinguistic and metapragmatic development, as a rationale for our study. Our analysis shows gender differences in the situations portrayed by children as humorous, allowing us to explore children identity as displayed in their compositions. In general, female participants picture themselves in embarrassing situations, while males show a great self-esteem, since their narratives represent themselves successfully overcoming all of the cultural shocks they face on their way to Mars.
Keywords: Humor; gender; metapragmatic competence; children.